FTTISI — the bedrock of Covid-19 infection control - Mohd Nordin, Musa; Rusli, Mohammad Farhan (Malay Mail Sdn Bhd, 2021)
"The FTTIS system Finds and Tests hotspots of Covid-19 outbreaks. Rapid Isolation of cases and quarantine of close contacts through Tracing is extremely critical. Isolation will only work if the rakyat, especially the B40, receive Support during the MCO period with food security and financial Support [4]"